Hand It to Dr Google: The Quality of Online Information on Ganglion Cysts. (January 2022) - Ji, Tianshu Angela; Wells, Neil; Ingledew, Paris-Ann
Background: The internet is becoming a common source of health information for hand surgery patients. This study evaluates the quality of web-based resources on ganglion cysts of the hand.Methods: We completed a search for "ganglion cyst" on 3 search engines (Google, Dogpile, and Yippy). The quality of the top-100 patient education websites was assessed using a validated internet rating tool. Websites were evaluated based on affiliation, accountability, currency, interactivity, website organization, readability, coverage, and accuracy.Results: Of the 100 websites, the majority (74%) had commercial affiliations. Only 34% of websites identified an author, and even fewer identified the authors' credentials (27%) or affiliations (26%). A third of the websites cited references, and less than half provided an update date. The average readability based on Flesch-Kincaid grade level was 9.2, and only 3% could be read at or below 6th grade reading level. Prevention was the most poorly covered topic at 13% due to omission. In all, 66% of the websites were completely accurate in terms of global accuracy. Websites were most likely to present inaccurate information on treatment, often failing to mention conservative treatment (watch-and-wait approach) or promoting the use of natural health products. We also found 5% of websites presented closed rupture of the ganglion cyst as a legitimate home remedy.Conclusions: The overall quality of online information on ganglion cysts is highly variable and may occasionally be harmful for patients. It is increasingly important for physicians to prompt patients about their internet use.